Changes in the incidence of lower urinary tract stones in Japan from 1965 to 1995 - Terai, Akito; Okada, Yusaku; Ohkawa, Tadashi; Ogawa, Osamu; Yoshida, Osamu (International journal of urology, 2000)
Background The changes over time of the annual incidence of lower urinary tract stones in Japan from 1965 to 1995 were analyzed. Methods Data on lower urinary tract calculi were ed from the past three nationwide surveys of urolithiasis, which covered nearly all major hospitals and urologists in Japan and enumerated all outpatient visits diagnosed as urolithiasis in the years 1965, 1975, 1985 and 1995. Chronological changes in the sex‐ and age‐related annual incidences of lower urinary tract stones and stone composition were estimated. Results Lower urinary tract stones were predominant in men 60 years of age or older. Between 1965 and 1995, the annual incidence has significantly decreased in men ≥ 60 years of age from 37.2 to 27.0 per 100 000 and significantly increased in women ≥ 60 years of age from 2.4 to 4.8 per 100 000. In men, an increased proportion of uric acid and calcium stones as well as a decreased frequency of infection stones is a phenomenon common to upper urinary tract stones. However, infection and calcium stones have been two major stone types in women. Conclusions In contrast to upper urinary tract calculi, the incidence of lower urinary tract stones has decreased over the last 30 years in men ≥ 60 years of age predisposed to this disease.